2015
DOI: 10.1017/s0022215115001425
|View full text |Cite
|
Sign up to set email alerts
|

Tinnitus and its relationship with muscle tenderness in patients with headache and facial pain

Abstract: In a population of patients with headache and craniofacial pain, tinnitus was related to increased cervical muscle tenderness and pericranial muscle tenderness scores, rather than to any particular form of headache.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 22 publications
2
28
0
Order By: Relevance
“…To our knowledge, a comprehensive analysis of the comorbidity of tinnitus and joint pain is absent in the literature. However, numerous reports in the literature have documented tinnitus and temporomandibular disorder, headache, and facial pain [24,25]. Thus, this could be the first study that statistically evaluates the comorbidity of tinnitus and various sites of joint pain.…”
Section: Discussionmentioning
confidence: 93%
“…To our knowledge, a comprehensive analysis of the comorbidity of tinnitus and joint pain is absent in the literature. However, numerous reports in the literature have documented tinnitus and temporomandibular disorder, headache, and facial pain [24,25]. Thus, this could be the first study that statistically evaluates the comorbidity of tinnitus and various sites of joint pain.…”
Section: Discussionmentioning
confidence: 93%
“…Only the latter articles were included, as they contained the most relevant information for this review. Consequently, a total of 22 independent articles were included in this study ( Akhter et al., 2013 ; Bernhardt et al., 2004 ; Bonaconsa et al., 2010 ; Buergers, Kleinjung, Behr, & Vielsmeier, 2014 ; Camparis, Formigoni, Teixeira, & De Siqueira, 2005 ; De Felicio, Melchior, Ferreira, & Rodrigues Da Silva, 2008 ; de-Pedro-Herraez, Mesa-Jimenez, Fernandez-de-Las-Penas, & de-la-Hoz-Aizpurua, 2016 ; Effat, 2016 ; Fernandes, de Godoi Goncalves, de Siqueira, & Camparis, 2013 ; Hilgenberg et al., 2012 ; Khedr et al., 2010 ; Kuttila, Kuttila, Le Bell, Alanen, & Suonpaa, 2005 ; Lee et al., 2016 ; Park & Moon, 2014 ; Parker & Chole, 1995 ; Pekkan, Aksoy, Hekimoglu, & Oghan, 2010 ; Peroz, 2003 ; Pezzoli et al., 2015 ; Ren & Isberg, 1995 ; Rocha & Sanchez, 2007 ; Rubinstein, Osterberg, Rosenhall, & Johansson, 1993 ; Tuz, Onder, & Kisnisci, 2003 ). No additional articles were identified from the reference lists of the articles ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…No studies were found in which tinnitus was explored in patients with and without CSD. Of the studies investigating the association between tinnitus and TMD, three studies examined patients with and without tinnitus, wherein both groups also complained about bruxism ( Camparis et al., 2005 ), disc displacements of the temporomandibular joint (TMJ; Ren & Isberg, 1995 ), or headache or facial pain ( Pezzoli et al., 2015 ). Most patients were recruited from general or specialized hospitals/ENT departments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations